2003
DOI: 10.1034/j.1399-6576.2003.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium combined with i.v. lidocaine for rapid tracheal intubation

Abstract: The combination of lidocaine (1.5 mg kg(-1)) and low-dose rocuronium (0.6 mg kg(-1)) along with propofol is clinically equivalent to succinylcholine, improves intubating conditions in 60 s and effectively blocks increases in heart rate after intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
0
20
0
7
Order By: Relevance
“…Rocuronium is a non-depolarizing, aminosteroid, neuromuscular blocker with an intermediate duration but fast onset of action, which differentiates it from the other non-depolarizing blockers and makes it an alternative agent to succinylcholine in situations of rapid-sequence induction [12][13][14] . The aim of this study was to evaluate, in an experimental model, the effects of procainamide in the neuromuscular transmission and its influence on the neuromuscular blockade produced by rocuronium and to investigate the probable mechanism of the interaction between procainamide and rocuronium.…”
Section: Influence Of Procainamide On the Neuromuscular Blockade Causmentioning
confidence: 99%
See 1 more Smart Citation
“…Rocuronium is a non-depolarizing, aminosteroid, neuromuscular blocker with an intermediate duration but fast onset of action, which differentiates it from the other non-depolarizing blockers and makes it an alternative agent to succinylcholine in situations of rapid-sequence induction [12][13][14] . The aim of this study was to evaluate, in an experimental model, the effects of procainamide in the neuromuscular transmission and its influence on the neuromuscular blockade produced by rocuronium and to investigate the probable mechanism of the interaction between procainamide and rocuronium.…”
Section: Influence Of Procainamide On the Neuromuscular Blockade Causmentioning
confidence: 99%
“…A potencialização dos efeitos da d-tubocurarina pela procainamida tem sido demonstrada 11 , porém ainda não existem estudos comparativos para demonstrar a interação da procainamida com outros bloqueadores neuromusculares atualmente empregados na prática clínica. O rocurônio é um bloqueador neuromuscular não-despolarizante aminoesteróide, com duração de ação intermediá-ria mas rápido início, característica que o diferencia dos demais bloqueadores não-despolarizantes e o torna um agente alternativo para a succinilcolina em situações de indução de seqüência rápida [12][13][14] . O objetivo deste estudo foi avaliar, em modelo experimental, o efeito da procainamida na transmissão neuromuscular e a sua influência no bloqueio neuromuscular produzido pelo rocurônio, investigando ainda o provável mecanismo da interação procainamida e rocurônio.…”
unclassified
“…There was no significant change in pulse rate in vecuronium group but rocuronium group shows a significant change in pulse rate. Yorukoglu D et al, 18 observed that with rocuronium mean arterial blood pressure decreased after induction of anesthesia ( P<0.01) compared with baseline and increased significantly after tracheal intubation compared with the levels after induction of anesthesia (P<0.01). Schramm WM et al, 19 concluded in their study that patients in the Rocuronium group showed significant increase in heart rate that might be due to a vagal blocking effect.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is consistent with several studies like. Booth MG et al, 14 Robertson EN et al, 15 Neilson K et al, 16 Misra M. N. et al, 17 Yorukoglu D et al, 18 and Schramm WM et al 19 Booth MG et al, 14 found increased heart rate by 36% in the Rocuronium group during the first minute following injection of Rocuronium, but remained stable in those patients who received Vecuronium. Robertson EN et al, 15 observed that rocuronium caused a 10-15% rise in mean arterial pressure and 5-10 % rise in heart rate whereas Vecuronium had no significant cardiovascular effects.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no significant difference between the groups. Yörükoğlu et al (19) evaluated the intubating conditions and hemodynamic changes associated with rocuronium and succinylcholine, after 2 mg kg -1 propofol induction. In that study, no significant difference was found in the HR values of patients, who were given 1.5 mg kg -1 lidocaine plus rocuronium.…”
Section: Discussionmentioning
confidence: 99%